American anti-Chinese racism during the Covid-19 crisis and its strategic functions - Vrečko Ilc, Blaž (Teorija in praksa, 2021)
The Covid-19 crisis that hit the USA especially hard was accompanied by intensified anti-Chinese racism fuelled by the anti-Chinese rhetoric used by the Trump Administration. Although Trump's political opponents blamed him for having mismanaged the pandemic response, the anti-Chinese stance was a bipartisan issue. The article aims to analyse anti-Chinese racism in its systemic and historical dimensions. It examines the nature and strategic utility of anti-Chinese racism for past, the Trump, and future administrations as well as for America's elites generally. It is shown that anti-Chinese racism was substantially transformed during the pandemic and above all utilised to address the general destabilisation of the US-dominated socio-political and socio-economic order both at home and globally. China's growing importance around the world and the potential domestic destabilisation of the US mean that the strategic utility of anti-Chinese racism may well remain important for some time to come.
Keywords: Covid-19; Epidemics; Epidemije; Foreign policy; protikitajski rasizem; Racism; Rasizem; sistemski rasizem; Trumpovo predsedovanje; Zunanja politika